RETIREMENT PREPAREDNESS AMONGST WORKING ADULTS IN KAZAKHSTAN - Bakhtgalieva, Aigerim; Chan Yin-Fah1, Benjamin; Binti Mohamad Alwie, Sueraya (Scientific Journal of Pedagogy and Economics, 2018)
Today, the topic related to the retirement planning and the future of a person at retirement age is relevant, because the aging of the nation is going on all over the world. All countries of the world are engaged in the study of this topic. However, for Kazakhstan, this topic is still not sufficiently developed, and there is a great potential for research and improvement. In Kazakhstan, the number of elderly people is also increasing, and retirement planning is important. This study aims to determine how the citizens of Kazakhstan plan for their retirement; their long-term care and what level of financial literacy they have in relation to pension accrual. In addition, it was clarified on what factors the final decision of people regarding retirement planning. The study was conducted in the form of interviews with 10 respondents. Each of them shared their opinion, experience and perspective on their financial matter in responding to retirement planning